Служба документаційного забезпечення діяльності бібліотеки: нові виклики в умовах інформаційного суспільства - Ковальчук, Наталія (Видавництво Львівської політехніки, 2019)
The publication is devoted to the attempt to define the specifics of the work of the documentation service of the library management in the information society. The economy, efficiency, unification, quality, computerization are determined as the factors that promote the efficiency of the service as well as the library.
Keywords: documentation service; library management; information society